In Vitro Changes of Blood and Postmortem Interval - Arıcan, Nadir; Dokgöz, Halis; Yorulmaz, Coşkun; Elmas, İmdat; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 2000)
In this study, the postmortem changes in blood cell count (leucocyte, erytrocyte, platelet) as a result of autolysis and putrefaction and the relation of the changes with postmortem interval(PMI) have been researched. The research is based on blood samples taken from 10 subjects of 20-40 age group, without oncological, hematological, or infectious diseases, and not placed in refrigirator after death and 40 alive subjects (Control group) with the similar crite ria which have been observed through in vitro process. With some intervals through 120 hours, sub-samples have been taken from both groups of main blood samples, and total WBC, RBC, PLT counts and differential WBC counts were performed with blood count device. Also, differential changes of WBC count in unit field of peripheric smears were observed simultaneously. As a result of this study, all parameters except total RBC and platelet counts of the case group and control group and also the correlation between the groups with PMI are found significant (p
Keywords: postmortem interval; leucocyte; platelet; erythrocyte